Multimedia-Based E-Flashcards for Letter Recognition in Early Primary Education - Putri Nabila Selvira; Rafidhah Hanum (LaKaspia, 2026)
Letter recognition constitutes a fundamental component of early literacy development and plays a critical role in supporting beginning reading and writing skills in primary education. Difficulties in distinguishing letter forms, particularly visually similar letters, may hinder students’ early reading progress and classroom participation. This study aimed to develop a multimedia-based e-flashcard learning medium and to examine its feasibility and effectiveness in supporting letter recognition among Grade 1 students. The study employed a research and development approach using the ADDIE model, followed by classroom implementation through a one-group pretest and posttest design involving 25 students. The developed e-flashcards integrated letter forms, supporting images, example words, and audio elements designed to reinforce visual recognition and letter–sound associations. Feasibility evaluation through expert validation demonstrated that the product met validity standards across media, content, and language domains. The effectiveness findings indicated a marked improvement in students’ letter recognition performance, reflected in the increase from pretest to posttest scores. Statistical analysis using a paired-samples t-test indicated a statistically significant difference between pretest and posttest results. These findings indicate that multimedia-based e-flashcards can function as a supportive instructional medium for strengthening letter recognition, particularly in addressing difficulties related to visually similar letters in early primary classrooms.